2016
DOI: 10.1371/journal.pone.0162773
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Lingual Nerve Course: A Human Cadaveric Study

Abstract: The lingual nerve is a terminal branch of the mandibular nerve. It is varied in its course and in its relationship to the mandibular alveolar crest, submandibular duct and also the related muscles in the floor of the mouth. This study aims to understand the course of the lingual nerve from the molar area until its insertion into the tongue muscle. This cadaveric research involved the study of 14 hemi-mandibles and consisted of two parts: (i) obtaining morphometrical measurements of the lingual nerve to three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 56 publications
3
40
0
2
Order By: Relevance
“…Hölzle et al reported that SD runs deep in the floor of the oral cavity without a relationship with the LN in 11.8 % of the cases [12]. Al-Amery et al found that LN was passing below the SD before rising again toward the ventral surface of the tongue in 12 out of the 13 of the cases, in one case the relationship was similar with the findings of Hölzle et al [1,12,15].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Hölzle et al reported that SD runs deep in the floor of the oral cavity without a relationship with the LN in 11.8 % of the cases [12]. Al-Amery et al found that LN was passing below the SD before rising again toward the ventral surface of the tongue in 12 out of the 13 of the cases, in one case the relationship was similar with the findings of Hölzle et al [1,12,15].…”
Section: Discussionsupporting
confidence: 60%
“…They also found the mean distance between the LN and alveolar ridge was 12.36 mm and the mean distance between the LN and the lower border of mandible was 12.03 mm [1].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations